2018
DOI: 10.1167/iovs.18-24938
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolomics Profiling of Glaucoma Points to Mitochondrial Dysfunction, Senescence, and Polyamines Deficiency

Abstract: Our results highlight a systemic and age-related mitochondrial defect in the pathogenesis of POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(81 citation statements)
references
References 37 publications
9
71
0
1
Order By: Relevance
“…The increased arginine concentration in POAG plasma was evidenced by three of the four data methods and was already reported in the targeted metabolomics study [7], together with that of methionine and tyrosine, which were also identified here by the univariate analysis, thus attesting the reproducibility of the results obtained with two different mass spectrometry approaches. Modification of arginine concentration may be related to the altered arginine/nitric oxide regulatory pathway that characterize glaucoma [20].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The increased arginine concentration in POAG plasma was evidenced by three of the four data methods and was already reported in the targeted metabolomics study [7], together with that of methionine and tyrosine, which were also identified here by the univariate analysis, thus attesting the reproducibility of the results obtained with two different mass spectrometry approaches. Modification of arginine concentration may be related to the altered arginine/nitric oxide regulatory pathway that characterize glaucoma [20].…”
Section: Discussionsupporting
confidence: 84%
“…Indeed, a study of the mouse DBA/2J model with high intra-ocular pressure has recently established the proof of concept of vitamin B3 therapeutic interest [15] to prevent glaucoma. Our current investigations in humans [7] together with the recent report in mice, argues in favor of a mitochondrial-related nicotinamide deficiency, contributing to the age-related vulnerability of the optic nerve in glaucoma pathogenesis. This statement is further reinforced by the fact that mitochondrial complex I deficiency was also reported in lymphoblasts from glaucoma patients [16], a fact that could be related to the decrease level of nicotinamide adenine dinucleotide (reduced form) (NADH) in these cells [17].…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In this respect, the lymphoblasts of patients with POAG showed a mitochondrial complex I deficiency reflecting a systemic mitochondrial impairment 4,5 . In addition, using targeted metabolomics on the plasma of POAG patients compared to controls, we have recently shown a metabolic profile combining the impaired utilization of energetic substrates and decreased levels of polyamines, attesting to mitochondrial dysfunction, and premature ageing 22 . Since nicotinamide is one of the main contributors to the regeneration of NAD through a salvage metabolic pathway, nicotinamide deficiency could reflect excessive age-related NAD consumption, which subsequently leads to complex I deficiency, and the energetic failure responsible for the degeneration of RGCs.…”
Section: Discussionmentioning
confidence: 99%